Reducing caesarean section rate in an urban hospital serving women attending privately in India - a quality improvement initiative - Abhishek Bhartia; Rinku Sen Gupta Dhar; Saru Bhartia (BMC, 2020)
Abstract Background In line with global trends, India has witnessed a sharp rise in caesarean section (CS) deliveries, especially in the private sector. Despite the urgent need for change, there are few published examples of private hospitals that have successfully lowered their CS rates. Our hospital, serving private patients too, had a CS rate of 79% in 2001. Care was provided by fee-for-service visiting consultant obstetricians without uniform clinical protocols and little clinical governance. Consultants attributed high CS rate to case-mix and maternal demand and showed little inclination for change. We attempted to reduce this rate with the objective of improving the quality of our care and demonstrating that CS could be safely lowered in the private urban Indian healthcare setting. Methods We hired full-time salaried consultants and began regular audit of CS cases. When this proved inadequate, we joined an improvement collaborative in 2011 and dedicated resources for quality improvement. We adopted practice guidelines, monitored outcomes by consultant, improved labour ward support, strengthened antenatal preparation, and moved to group practice among consultants. Results Guidelines ensured admissions in active labour and reduced CS (2011 to 2016) for foetal heart rate abnormalities (23 to 5%; p < 0.001) and delayed progress (19 to 6%; p < 0.001) in low-risk first-birth women. Antenatal preparation increased trial of labour, even among women with prior CS (28 to 79%; p < 0.001). Group practice reduced time pressure and stress, with a decline in CS (52 to 18%; p < 0.001) and low-risk first-birth CS (48 to 12%; p < 0.001). Similar CS rates were maintained in 2017 and 2018. Measures of perinatal harm including post-partum haemorrhage, 3rd-4th degree tears, shoulder dystocia, and Apgar < 7 at 5 min were within acceptable ranges (13, 3, 2% and 3 per thousand respectively in 2016-18,). Conclusions It is feasible to substantially reduce CS rate in private healthcare setting of a middle-income country like India. Ideas such as moving to full-time attachment of consultants, joining a collaborative, improving labour ward support, providing resources for data collection, and perseverance could be adopted by other hospitals in their own journey of moving towards a medically justifiable CS rate.